An Experimental Investigation of the End-to-End QoS of the Apple Darwin Streaming Server - Luca De Cicco; Saverio Mascolo; Vittorio Palmisano; Jarmo Harju; Geert Heijenk; Peter Langendörfer; Vasilios Siris (Wired/Wireless Internet Communications, 2008)
Video content distribution over the traditional best-effort, store-and-forward Internet Protocol is of ever increasing importance due to the great success of new web services such as personal video broadcast or television over IP (IPTV). In this paper we investigate the end-to-end quality of service (QoS) that is provided by the Apple Darwin Streaming Server and the Quick-Time client player in the presence of time-varying available bandwidth and multiple concurrent streaming sessions. The considered end-to-end QoS parameters are the loss rates and the friendliness experienced when the available bandwidth changes and when multiple QuickTime streaming sessions and/or TCP sessions compete in order to obtain a bandwidth share.